Desenvolvimento de material didático digital para apoio ao ensino da contabilidade introdutória na educação profissional e tecnológica - Londero, Angelica Scremin (2021)
This master's research was developed within the research line Innovation for EPT of the Programa de Pós-Graduação em Educação Profissional e Tecnológica (CTISM/UFSM), and presents as a general objective to develop digital teaching materials (DTM to support the teaching practices of teachers of Introductory Accounting. This objective is justified by the fact that Accounting is an area of education with scarce digital didactic materials for use by teachers in their teaching practices, especially in technical courses, in which teaching has a more practical approach and is connected to the reality of the labor world. The authors who supported this study were: Andrade (2015); Peleias (2006, 2007); Felder-Silvermann (1988, 2002); Amiel (2018), Filatro (2018), among others. An applied research was chosen, since it is a study with the purpose of solving problems identified in the scope of the researcher's experience. As a result, a website was developed, called REA_CONT, of free and open access, which brings together a collection of activities and varied content, which will serve as support for teachers, as well as the site also provides tutorials so that teachers, who prefer to develop their own teaching materials, have an initial path to support themselves. The site was qualitatively evaluated by teachers and students from higher and technical education, and the data collected served to attest that the research achieved its proposed objective, which contributes to the teachers' teaching practices and to the students' study and review of content. The work will continue, expanding the development of materials for areas other than Introductory Accounting, and for this it already has scholarship holders for the development of materials.